Leptotrombidium (Acari: Trombiculidae) of the World - Stekolnikov, Alexandr A. (Zootaxa, 2013)
The chigger mite genus Leptotrombidium Nagayo, Miyagawa, Mitamura and Imamura, 1916 is reviewed using literature data. For 340 larval species brief diagnoses, synonymy, data on type hosts and type localities are provided. The genus is divided into species-groups based on morphological evidence enabling easier establishment of group-membership of unknown specimens in the future. Some species groups are supported by a hierarchical cluster analysis with multiscale bootstrap resampling applied to a matrix including 335 species and geographic morphotypes and 19 standard quantitative characters. Six new species from mammalian hosts are described: L. aenigmami sp. nov., L. abramovi sp. nov., L. tikhonovi sp. nov., L. bochkovi sp. nov., L. laoense sp. nov., and L. megaloti sp. nov. from Laos. Seven names created by Vercammen-Grandjean and Langston (1976) for infrasubspecific entities are applied to species with the same descriptions: Leptotrombidium tenompaki sp. nov., L. kinabalui sp. nov., L. megabodense sp. nov., L. minului sp. nov., L. ului sp. nov., L. megalangati sp. nov., and L. saigoni sp. nov. A new replacement name is proposed: L. ushi nom. nov. pro L. hsui Wu, Yang and Li, 1999 (praeocc. Yu, Yang and Gong, 1986). Nineteen new synonyms and 7 new combinations are proposed: Leptotrombidium (= Hsuella Wang, Li and Shi, 1989, syn. nov.; = Leptotrombidium (Monosigmum) Wen, 2001, syn. nov.), L. deliense (Walch, 1922) (= L. deliense sinense Wen and Chen, 1984, syn. nov.; = L. deliense microsetosa Zhao, Tang and Mo, 1986, syn. nov.), L. sialkotense Vercammen-Grandjean and Langston, 1976 (= L. jishoum Wen, Li, Zhang and Liao, 1988, syn. nov.), L. imphalum Vercammen-Grandjean and Langston, 1976 (= L. imphalum sabahense Vercammen-Grandjean and Langston, 1976, syn. nov.; = L. chiangraiensis Tanskul and Linthicum, 1997, syn. nov.), L. wenense Wu, Wen, Yang and Wu, 1982 (= L. kaohuense Li, Wang and Chen, 1997, syn. nov.), L. longimedian Brown, 1992 (= L. mindanensis Brown, 1992, syn. nov.), L. silvaticum Hushcha and Schluger, 1967 (= L. pakistanum Vercammen-Grandjean and Langston, 1976, syn. nov.), L. cricethrionis Wen, Sun and Sun, 1984 (= L. rusticum Yu, Yang and Gong, 1986, syn. nov.), L. intermedium (Nagayo, Mitamura and Tamiya, 1920) (= Trombicula (L.) daisen Kumada and Sasa, 1953, syn. nov.; = Trombicula hiranumai Kanda, 1942, syn. nov.), L. fletcheri (Womersley and Heaslip, 1943) (= L. fletcheri francolini Wen and Xiang, 1984b, syn. nov.), L. apertum Kudryashova, 1979 (= L. sorosi Kharadov, 1995, syn. nov.; = L. tolaicus Kharadov, 2000, syn. nov.), L. turdicola Vercammen-Grandjean and Langston, 1976 (= L. muntiaci Xiang and Wen, 1984d, syn. nov.; = L. suense Wen, 1984g, syn. nov.), L. paradux Vercammen-Grandjean and Langston, 1976 (= L. montanum Stekolnikov, 2004, syn. nov.), L. hubeiense (Wang, Li and Shi, 1989) comb. nov. from Hsuella, L. dunqingi (Liu, Xiang and Ma, 2003) comb. nov. from Hsuella, L. nainae (Kharadov, 1990) comb. nov. from Montivagum, L. mongolicum (Kudryashova, 1988) comb. nov. from Montivagum, L. kunitzkyi (Kudryashova, 1988) comb. nov. from Montivagum, L. alaicum (Kharadov, 1994) comb. nov. from Montivagum, and Lorillatum nudisensillum (Yu, Gong and Tao, 1981) comb. nov. from Leptotrombidium. A key to Leptotrombidium species is provided.